ASOCIACIÓN ENTRE TALLA MATERNA BAJA Y EL APGAR DEL RECIÉN NACIDO POR VÍA VAGINAL - Quito Santos y Col., César (2019)
The study present to determine the asociation between small maternal height and vaginal delivered baby just born apgar. We revised perinatal clinical histories corresponding to parities ocurred from January 1st, 2003 to December 31st, 2003 in HRDT. During the study period 2785 births take place, howerer only 1781 were included according to the inclusion criteria. 1359 born from non-small maternal height (>1,5m), while 422 born from small mothers (≤ 1,5m). In the 285 newborns delivered by vaginal way from small mothers we found 7.7% with low apgar at 1st minute and 2.5% at 5th minute. In the newborn group from non-small mother, only 1123 were delivered by vaginal way, we found low apgar in 3,9% and 0,45% at first minute and 5th minute respectively. In Conclusions the vaginal birth, there is a higly significative corelation between small maternal height and low apgar in newborns,both at 1st and 5th minutes.